IMPROVING THE SAFETY OF RAILWAY AUTOMATION AND REMOTE CONTROL SYSTEMS (Transport systems and technologies, 2018)
The article discusses improving the functional safety of automation systems, telemechanics and communications as a central problem in ensuring traffic safety in railway transport. The solution to this problem is based on the integrated implementation of scientific, technical, organizational and operational, ergonomic and economic aspects. The analysis of domestic and foreign experience in the field of creation of the compressed gas fuel generator has shown the main trends in the development of traffic safety systems. Scientific novelty consists in the development of the main provisions of the concept and principles of building a multi-level control system and ensuring the safety of train traffic.An analysis of domestic and foreign experience in the field of the creation of the SRAR has established that the main trends in the development of traffic safety systems are:– multilevel structure of the security system, depending on the intensity of the train movement and the equipment of the sites by floor devices;– transfer of performance of control functions and safety on board of a locomotive;– use of high-speed communication channels (point channel and radio channel)– development of objective methods for controlling the driver's waking to evaluate his physiological parameters;– use of satellite navigation systems;– creation of a unified network for the transmission of information with additional requirements regarding the reliability and timing of messages, including for radio channels.The following trends were identified for the development of traffic safety systems:– the multilevel structure of the security system, depending on the equipment of the sections by the traveling devices;– transfer of the performance of control and safety functions on board the locomotive;– use of high-speed communication channels (point-to-point communication channel and radio channel)– the development of objective methods of monitoring the wakefulness of the driver to assess its physiological parameters;– the use of satellite navigation systems to calculate the coordinates and speed of the locomotive.
Keywords: functional safety, traffic safety, relays, reliability, railway automation and telemechanics systems